The prominent role of miR-942 in carcinogenesis of tumors - Negar Yadegar; Zahra Dadashi; Kimiya Shams; Mahdis Mohammadi; Mahya Abyar; Milad Rafat (Advanced Biomedical Research, 2022)
As a family of short noncoding RNAs, MicroRNAs have been identified as possible biomarkers for cancer discovery and assist in therapy control due to their epigenetic involvement in gene expression and other cellular biological processes. In the present review, the evidence for reaching the clinical effect and the molecular mechanism of miR-942 in various kinds of cancer is amassed. Dysregulation of miR-942 amounts in different kinds of malignancies, as bladder cancer, esophageal squamous cell carcinoma, breast cancer, cervical cancer, gastric cancer, colorectal cancer, Kaposi's sarcoma, melanoma, Hepatocellular carcinoma, nonsmall-cell lung cancer, oral squamous cell carcinoma, osteosarcoma, ovarian cancer, pancreatic ductal adenocarcinoma, renal cell carcinoma, and prostate cancer has stated a considerable increase or decrease in its level indicating its function as oncogene or tumor suppressor. MiR-942 is included in cell proliferation, migration, and invasion through cell cycle pathways, including pathways of transforming growth factor-beta signaling pathways, Wnt pathway, JAK/STAT pathway, PI3K/AKT pathway, apoptosis pathway, hippo signaling pathway, lectin pathway, interferon-gamma signaling, signaling by G-protein coupled receptor, developmental genes, nuclear factor-kappa B pathway, Mesodermal commitment pathway, and T-cell receptor signaling in cancer. An important biomarker, MiR-942 is a potential candidate for prediction in several cancers. The present investigation introduced miR-942 as a prognostic marker for early discovery of tumor progression, metastasis, and development.